2002
DOI: 10.1128/jcm.40.1.287-291.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Real-Time, Quantitative PCR with Molecular Beacons to Nested PCR and Culture Methods for Detection ofMycobacterium aviumsubsp.paratuberculosisin Bovine Fecal Samples

Abstract: An automated PCR with fluorescent probes (molecular beacons) detected Mycobacterium avium subsp. paratuberculosis in bovine feces. When the PCR was compared with culture in testing 41 fecal samples, kappa scores of 0.94 to 0.96, a sensitivity of 93 to 96%, and a specificity of 92% were obtained. Results were quantitated by using a standard curve derived from a plasmid containing IS900. A minimum quantity of 1.7 ؋ 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 35 publications
2
56
2
1
Order By: Relevance
“…Although PCR-based screening methods performed on (pooled) faecal samples are nowadays offered in some countries, a combination of direct examination of ZN-stained smears, serological methods and culture is still mainly used routinely by veterinary diagnostic laboratories for identifying infected farms (Harris and Barletta, 2001). The rationale for using DNA-based Mapspecific assays on faecal material stems from the expected higher sensitivity and faster performance compared to the culture (Bogli-Stuber et al, 2005;Fang et al, 2002;Huntley et al, 2005;Tasara et al, 2005;Tripathi et al, 2006). Using this experimental Map infection model allowed us to monitor Map excretion over almost 3 years time in the same Map exposed animals and to compare the performance of conventional methods with our DNA-based detection assay on serial faecal samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PCR-based screening methods performed on (pooled) faecal samples are nowadays offered in some countries, a combination of direct examination of ZN-stained smears, serological methods and culture is still mainly used routinely by veterinary diagnostic laboratories for identifying infected farms (Harris and Barletta, 2001). The rationale for using DNA-based Mapspecific assays on faecal material stems from the expected higher sensitivity and faster performance compared to the culture (Bogli-Stuber et al, 2005;Fang et al, 2002;Huntley et al, 2005;Tasara et al, 2005;Tripathi et al, 2006). Using this experimental Map infection model allowed us to monitor Map excretion over almost 3 years time in the same Map exposed animals and to compare the performance of conventional methods with our DNA-based detection assay on serial faecal samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, their specificity is compromised by close antigenic similarity between Map and other mycobacteria (Collins, 1996;Manning and Collins, 2001). PCR methods have made the rapid identification of Map in clinical samples possible, by reducing detection time (Englund et al, 1999;Fang et al, 2002;Ikonomopoulos et al, 2004;Motiwala et al, 2003Motiwala et al, , 2004Rajeev et al, 2005). In most studies, the main DNA target has been the insertion sequence IS900, initially considered to be a Map-specific marker (Green et al, 1989).…”
mentioning
confidence: 99%
“…Pinedo et al (2008) found that when comparing PCR tests with bacteriological culture and ELISA, Kappa values were 0.39 and 0.01, respectively. In contrast, Fang et al (2002), when correlating IS900 Q-PCR with bacteriological culture, a Kappa value of 0.94 was found. In this study, Kappa values in the first, second and fourth samplings ranged from 0.53 to 0.73 indicating a moderate correlation, although the Kappa value in third sampling reached 0.22 indicating a fair correlation.…”
Section: Samplingmentioning
confidence: 90%
“…Quantification of amplicon copies by q-PCR in DNA samples taken from bovine feces positive to IS900. signs of the disease (Park et al, 2016;Fang et al, 2002). Previously, Khol et al (2010), had followed for 380 days a 2.5 year-old cow that had become naturally infected with Map, sampling feces on 9 occasions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation